Transversus abdominis plane block as a component of anesthesia in kidney transplantation - A. V. Shabunin; E. P. Rodionov; P. A. Drozdov; A. A. Malyshev; B. A. Smolev; A. A. Efanov; S. A. Fedorishchev; R. I. Malashenko; S. A. Astapovich; E. A. Lidzhieva (Трансплантология (Москва), 2024)
Aim. To evaluate the safety and efficacy of the transversus abdominis plane block in kidney transplantation from deceased donor.Material and methods. The first stage included a retrospective comparative analysis of the results using the transversus abdominis plane block in renal transplantation. Group I (n=30) included patients who underwent transversus abdominis plane block after kidney transplantation; in comparative group II (n=58) the TAP-block wasn’t performed. We assessed the daily requirement for trimeperidine on the first day after kidney transplantation. The second stage was a prospective randomized placebo-controlled study. The patients were randomly divided into 2 groups with respect to whether the transversus abdominis plane block was provided with an active drug, or placebo was used; so the sodium chloride 0.9% was injected into the transversus abdominis plane in the intermuscular fascial plane between the internal oblique and transversus abdominis muscle in patients of Group III (n=31), and a local anesthetic was injected in patients of Group IV (n=34).) The daily requirements for trimeperidine, tramadol were assessed as well as the pain severity according to visual analogue scale at 1, 6, 12, 24 hours after surgery, the incidence of adverse events in the gastrointestinal tract; and several laboratory parameters (cortisol, interleukin-1, interleukin-6) related to pain syndrome were analyzed.Results. As a result of pseudorandomization, 17 cases were included in each of two retrospective stage, which were comparable in terms of patients' main characteristics (p>0.05). The daily requirement for trimeperidine in the transversus abdominis plane block group (Group I) was lower than in the comparison group with a trend toward statistical significance (p=0.07). The median daily dose of trimeperidine in Group III (placebo control) was 59.5 mg (interquartile range: 51.5–72.0), which was higher than in Group IV (45.5 mg; interquartile range: 38.5–62.0) (p=0.039). The postoperative pain severety assessed by visual analogue scale was also statistically significantly higher in group III at the timepoint of 12 hours after surgery, making 4.0 points (interquartile range: 2.5–5.0) versus 1.5 points (interquartile range: 0.5–2.5) in group VI (p=0.015). There were no differences between the groups in pain severity at 1, 6, and 24 hours after surgery. The daily requirement for tramadol was also statistically significantly higher in Group III, amounting to 50 mg (interquartile range: 0–100) versus 0 (interquartile range: 0–55 mg) in the active drug Group IV (p=0.045).Conclusion. Our study showed that the use of the transversus abdominis plain block was safe and effective, yielding encouraging results, which demonstrated a clinically significant reduction in the need for opioid analgesics and in the incidence of adverse events in the postoperative period after transversus abdominis plane block which contributes to the early activation of patients. Therefore, further studies are needed to improve the package of multimodal perioperative analgesia after kidney transplantation.